2018
DOI: 10.3390/ijms19103175
|View full text |Cite
|
Sign up to set email alerts
|

ITGB1b-Deficient Rare Minnows Delay Grass Carp Reovirus (GCRV) Entry and Attenuate GCRV-Triggered Apoptosis

Abstract: Integrin β-1 (ITGB1) is a transmembrane protein belonging to the integrin family and it plays an important role in viral entry. In this study, the itgb1b gene of the rare minnow, Gobiocypris rarus, was cloned and analyzed. To investigate the possible role of itgb1b on grass carp reovirus (GCRV) infection, we generated an ITGB1b-deficient rare minnow (ITGB1b−/−) using the CRISPR/Cas9 system. Following stimulation with GCRV, the survival time of the -ITGB1b−/− rare minnows was extended in comparison to the wild-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 49 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Virus entry into animal cells, the first step to launch a disease, is initiated by attachment to receptors and followed by penetration through (non-enveloped viruses) or fusion with (enveloped viruses) cellular membranes [14]. Pioneering studies have suggested that tight crosstalk between viral structure proteins (e.g., VP5, VP7, VP35) and host machinery (e.g., endosome, microtubules, dynamin, receptors, HSPs) are involved in the viral entry of GCRV infection [15][16][17][18][19][20][21]. However, our understanding of the temperature-dependent GCRV pathogenesis is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…Virus entry into animal cells, the first step to launch a disease, is initiated by attachment to receptors and followed by penetration through (non-enveloped viruses) or fusion with (enveloped viruses) cellular membranes [14]. Pioneering studies have suggested that tight crosstalk between viral structure proteins (e.g., VP5, VP7, VP35) and host machinery (e.g., endosome, microtubules, dynamin, receptors, HSPs) are involved in the viral entry of GCRV infection [15][16][17][18][19][20][21]. However, our understanding of the temperature-dependent GCRV pathogenesis is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…[82][83][84] Other challenges may include ancestral whole-genome duplication and mosaicism. [85][86][87][88][89][90][91] Mosaicism occurs when CRISPR/Cas nucleases retain activity after the first event of embryo cleavage, resulting in varying combinations of mutations among cell lineages. 92 All teleosts went through three rounds of genome duplication throughout vertebrate evolution.…”
Section: Clustered Regularly Interspaced Palindromic Repeats/cas9mentioning
confidence: 99%
“…Fish infected with GCRV produce a symptom reaction 4 days after infection. After 5-7 days, the fish show obvious hemorrhagic symptoms, and the fish population enters the peak of mortality [102]. Because of its high risk, wide prevalence, and long onset season, this virus has been the focus of research on fish viruses, but there is not yet an effective treatment [103].…”
Section: Medicinal Plants Against Gcrvmentioning
confidence: 99%